Herding Community: Entanglement in Of Horses and Men - McKinnon, Ann Marie (Humanimalia, 2020)
The Icelandic horse in the film Of Horses and Men is an individual understood on the basis of what it does, a biosocial becoming in a specific geography, society, and historical moment. The horse is a film actor and an agent and, seen through the visual repetition of the gaze of the horse in the film, offers a clear example of entangled agencies – a herd of human and non-human animals – that co-create their Icelandic home. This creaturely gaze emphasizes the relations between human and animal, undoes the conventional anthropocentric bias of the gaze in cinema, and informs an ethics that relies on the materiality and vulnerability of all living bodies.